Stability Indicating Determination of Human Growth Hormone by Novel SE–LC Method. (4th December 2019) - Rezk, Mamdouh R; Shehata, Mostafa A; Mohamed, Marwa F; Fathalla, Faten Abdel Aziz
Abstract: A selective, rapid size-exclusion chromatographic method was developed and validated for the separation of the human growth hormone (hGH) somatropin from its high-molecular-weight aggregates. Separation was achieved using a nontoxic mobile phase compared with the official method of the European Pharmacopoeia that uses 2-propanol in a mobile phase. The developed method used a YMC-Pack Diol (YMC Karasuma, Kyoto, Japan; 300 × 8.0 mm, 5 μm) analytical column. The mobile phase was formed with a pH 7phosphate buffer that was pumped at a flow rate of 1 mL/min with UV detection at 214 nm. The overall run time was 20 min and the average retention times were found to be 10.21 min for the monomer peak, 9.52 min for the dimer peak, and 9.14 min for the higher aggregate. This method was validated in terms of selectivity, linearity, and intra- and interday variations according to the International Conference on Harmonization guidelines. The developed method was applied as a rapid tool for evaluating the stability of stressed samples of hGH subjected to different temperature, agitation, and repeated freeze–thaw cycles. The developed method was successfully applied for the assessment of the quality and quantity of hGH during downstream processing, formulation, and storage.